Magnetic fields on young, moderately rotating Sun-like stars II. EK Draconis (HD 129333) - VIDOTTO, ALINE (My University, 2017)
The magnetic fields, activity and dynamos of young solar-type stars can be empirically studied using time-series of spectropolarimetric observations and tomographic imaging techniques such as Doppler imaging and Zeeman Doppler imaging. In this paper we use these techniques to study the young Sun-like star EK Draconis (Sp-Type: G1.5V, HD 129333) using ESPaDOnS at the Canada-France-Hawaii Telescope and NARVAL at the T\`elescope Bernard Lyot. This multi-epoch study runs from late 2006 until early 2012. We measure high levels of chromospheric activity indicating an active, and varying, chromosphere. Surface brightness features were constructed for all available epochs. The 2006/7 and 2008 data show large spot features appearing at intermediate-latitudes. However, the 2012 data indicate a distinctive polar spot. We observe a strong, almost unipolar, azimuthal field during all epochs that is similar to that observed on other Sun-like stars. Using magnetic features, we determined an average equatorial rotational velocity, \Omega_eq, of 2.50 +/- 0.08 rad/d. High levels of surface differential rotation were measured with an average rotational shear, \Delta\Omega, of 0.27 +0.24-0.26 rad/d. During an intensively observed 3-month period from December 2006 until February 2007, the magnetic field went from predominantly toroidal ( approx. 80%) to a more balanced poloidal-toroidal (approx. 40-60%) field. Although the large-scale magnetic field evolved over the epochs of our observations, no polarity reversals were found in our data
PUBLISHED
Keywords: magnetic fields; magnetic fields